Multiple hypotheses and their credibility in on-line fault diagnosis. - Juhwan Jung (IEEE Transactions on power delivery)
In this study, a new method that handles multiple hypotheses is presented for fault diagnosis using sequence of event recorders (SERs). To quantify the certainty of hypotheses, a method to calculate their credibility is provided. The proposed techniques are integrated in a generalized alarm analysis module (GAAM) and have been tested with numerous scenarios from the Italian power system